Analysis of factors influencing non-Muslims to become customers of Islamic banks - Saputri, Shinta Dewi; Rofiuddin, Mohammad (Fakultas Ekonomi dan Bisnis Islam UIN Salatiga, 2023)
The growth of Islamic banking has begun to infiltrate many sectors of society, attracting the desire of non-Muslim communities to become customers of Islamic banks. The purpose of this study to determine what factors can influence the decisions and interests of non-Muslim communities to become customers in Islamic banks. The sample used in this study amounted to 75 non-Muslim respondents in the Ungaran area with a random sampling technique. The method used is Moderated Regression Analysis. The results show that products and promotions harm decisions, word of mouth and interest have a significant positive effect on non-Muslim community decisions, products and promotions have a positive effect on interest for non-Muslim communities, word of mouth negatively affects interest, interest can mediate products with decisions, interest cannot mediate promotion and word of mouth on decisions.